Gender, Age and Language Familiarity: The Sociolinguistics of the Use of Americanisms in a University Campus - Adedeji, Kofo Ajibola (NIU Journal of Humanities, 2020)
The aim of this paper is to establish aspects of the sociolinguistic profile of Nigerians, specifically Nigerian undergraduates of the University of Lagos in Southwest Nigeria regarding the use of American and British English lexis and grammatical/structural forms. The impetus for this study is the observation of an increase in the use of American English in the face of the British norm-dependency official status of Nigeria. Data was collected from a hundred Nigerian university undergraduates of the University of Lagos aged 16-30 years old. Salient sociolinguistic information such as gender, age and language familiarity were juxtaposed with the usage of the two geographical variants of English. Two major outcomes are: American lexical and grammatical norms and expressions are more frequently used than British forms; female undergraduates use these Americanisms more often than their male cohorts. Keywords: Gender, Age, Sociolinguistics, Undergraduates, Americanisms